The effects of oil shocks on government expenditures and government revenues nexus in Nigeria (with exogeneity restrictions) - Adebayo Adedokun (Future Business Journal, 2018)
The study employed data from 1981 to 2014 to investigate the effects of oil shocks (price and revenue) on the dynamic relationship between government revenues and government expenditures in Nigeria and how it transmits effects on major macroeconomic variables using structural VAR (SVAR) on key variables, and also employed unrestricted VAR and Vector Error Correction (VEC) Models on expanded number of variables. The results of SVAR show that oil price shocks could not predict the variation in government expenditure in the short-run, while the predictive power of oil revenue shocks is very strong both in the short-run and in the long-run. The VAR and VECM also substantiate the results of SVAR and provide further insight which shows that short-run fiscal synchronization hypothesis is evidenced between the oil revenues and total government expenditures, while spend-tax hypothesis exists in the long-run between total expenditures and total revenues. It is also evidenced that oil shocks highly affect policy variables in the short-run and transfer the effects on the other macroeconomic variables in the long run. Thus, the study suggests expedient government actions to redirect the economy from oil revenue dependency towards diversifications along other less volatile sources of revenues so as to prevent long-run transmission of effects of oil shocks on broader macroeconomic variables.
Keywords: 650; Nigeria government expenditures; Oil prices; Oil revenues; Oil Shocks